AS MULHERES NA POLÍTICA BRASILEIRA: OS ANOS DE CHUMBO - Ridenti, Marcelo Siqueira [UNESP] (Departamento de Sociologia da Faculdade de Filosofia, Letras e Ciências Humanas da Universidade de São Paulo, 1990)
This paper attempts to clarify the political participation of Brazilian women in the sixties and the beginning of the seventies. Their struggle took diferent ways, for or against the military dictatorship. The paper presents data about women's integration in left wing groups, specially in urban guerrilla. Many women have taken place of these groups, mainly young graduates and students, though there were many more men involved with armed struggle against the military government. Women's militancy in guerrilla organizations has not been properly feminist, but it meant a step towards women's liberation, particularly if compared with organized militancy of right wing women, who supported the military government, defending their traditional status of ives, mothers and housewives'.

O artigo aponta a participação política diferenciada das mulheres brasileiras nos anos 60 e início dos 70, a favor ou contra a ditadura militar. São analisados dados estatísticos sobre a participação feminina nas organizações políticas clandestinas de esquerda em geral, e nos grupos guerrilheiros em particular. Esses contaram com a participação de várias mulheres, principalmente jovens intelectualizadas, ainda que em número muito inferior à participação masculina. A militância feminina nas organizações de combate armado à ditadura, mesmo que não se revestisse de caráter especificamente feminista, foi um momento de avanço na liberação da mulher, especialmente se essa militância for comparada com aquela das mães-esposas-donas-de-casa que se organizaram a favor do golpe de 1964.
The women in the Brazilian politics: the plumb years
Keywords: Brazil: women; left wing; sixties; military dictatorship; Brasil: mulheres; esquerda; anos 60; ditadura militar